PENGENALAN CARA MERANCANG VOICE IP (VOIP) PADA SISWA SISWI SMK WALI SONGO PECANGAAN - Adi Sucipto; R. Hadapiningradja Kusumodestoni; Akhmad Khanif Zyen (Universitas Muhammadiyah Semarang, 2015)
Voice over Internet Protocol, or better known as VoIP is a technology that uses the Internet Protocol to provide electronic voice communication and real-time, this technology makes the Internet media in order to make long-distance voice communications directly. Analogue voice signals, as you hear when communicating on the phone in the form of data analaog then converted into digital data and transmitted over the network in the form of data packets in real time.The use of voice over internet Procotol in a company or institution is very useful because in addition to much cheaper, using existing data networks, cabling is much more simple, more flexible and future development can be combined with the existing telephone network. Seeing the importance of the benefits of science and technology of voice over internet protocol for society in general and vocational students majoring in Computer Engineering and Networks (TKJ) in particular, one vocational school that has the Network Computer Engineering Department located in the district of Jepara regency Pecangaan is SMK Walisongo, the education and training on designing free calls using VOIP is very important to be disseminated and implemented.Keywords: VoIP, Internet Phone, Computer Networking